A Study to Assess the Effectiveness of Structured Teaching Program on Knowledge Regarding Breastfeeding Positioning Among Postnatal Mothers in Selected Community Areas in Kanpur - Divya Dwivedi; Muskan Chandra; Laxmi Devi; Arsh Faruqui; Seema Pal; Ajay Vishwakarma (International Journal of Women's Health Nursing And Practices, 2026)
Breastfeeding plays a crucial role in promoting infant health by providing complete nutrition, enhancing immunity, and strengthening maternal–infant bonding. Despite its benefits, many postnatal mothers experience challenges, such as nipple pain, breast engorgement, fatigue, and ineffective feeding, often due to improper breastfeeding positioning and poor latching techniques. Limited awareness and lack of structured education further contribute to these difficulties. Educating postnatal mothers on correct breastfeeding positioning is, therefore, essential to improve their knowledge, encourage correct practices, and support successful breastfeeding outcomes. This study aimed to assess the pre-test and post-test knowledge of postnatal mothers regarding breastfeeding positioning, evaluate the effectiveness of a structured teaching program, and determine the association between pre-test knowledge scores and selected demographic variables. A quantitative pre-experimental one-group pre-test post-test design was adopted. The study was conducted among 40 postnatal mothers selected through purposive sampling from an urban area of Kanpur, Uttar Pradesh. Data were collected using a self-structured questionnaire to assess knowledge on breastfeeding positioning. Following the pre-test, a structured teaching program with demonstration was administered, and a post-test was conducted to evaluate knowledge gain. The findings revealed that most of postnatal mothers were aged between 20–25 years (60%), had primary level education (45%), were homemakers (80%), multiparous (65%), and belonged to joint families (65%). Most participants had normal vaginal deliveries (47.5%) and were residents of rural areas (70%). In the pre-test, 20% of mothers demonstrated poor knowledge regarding breastfeeding positioning, whereas in the post-test, 80% of mothers achieved good knowledge levels. The mean knowledge score increased from 13.45 in the pre-test to 22.42 in the post-test, with a mean difference of 8.97. The paired t-test value of 4.44 indicated a statistically significant improvement in knowledge following the structured teaching program. The study concluded that the structured teaching program was effective in improving the knowledge of postnatal mothers regarding breastfeeding positioning, thereby emphasizing the importance of educational interventions in promoting optimal breastfeeding practices.
Keywords: Breastfeeding positioning; breastfeeding practices; knowledge assessment; postnatal mothers; structured teaching program